Congenital lobar emphysema: a 10-year case series review - André Assunção; Pedro Miragaia; Filipa Flôr-de-Lima; Susana Guimarães; Gustavo Rocha; Catarina Ferraz; Inês Azevedo (Portuguese Journal of Pediatrics)
Introduction and Objectives: Congenital lobar emphysema (CLE) is a rare congenital lung malformation that causes one or more pulmonary lobes to overinflate as a result of an air trapping-like mechanism and it may cause progressive respiratory distress. It is diagnosed in one in every 20,000 - 30,000 neonates. Diagnosis is usually made postnatally, with most cases identified in the first six months of life, but advances in ultrasound technology have allowed for some prenatal diagnosis. We report on the presentation, diagnostic methods, and management of a series of cases of CLE. Methods: Review of electronic files of patients diagnosed with CLE, over the past 10 years. Results: We identified four patients diagnosed with CLE: three female and one male. Two of these patients were diagnosed with CLE prenatally and remained asymptomatic for the entire recorded period, and the other two developed symptoms soon after birth. Chest radiographic imaging was performed in all four patients and a CT scan was carried out in three cases. The symptomatic cases required lobectomy and follow-up showed a slight decrease in residual volumes, total lung capacity, and forced expiratory volume, with no long-term pulmonary dysfunction. Discussion: Prenatal diagnosis of CLE is becoming more feasible with advances in imaging technology. In our population, we observed an inverted male-to-female ratio. Patients may remain asymptomatic and conservative management is advocated for such cases. When patients start to develop symptoms, there are progressive signs of increasing respiratory distress and, for these cases, surgery is recommended, with open thoracotomy being the preferred approach. Post-surgical complications are minimal and long-term pulmonary function remains stable.